(untitled) (Medical Forum Monthly, 2025)
Objective: To explore nurses’ attitudes toward family participation and collaboration in the care of hospitalized adult patients. Additionally, it sought to identify any correlations between these attitudes and the nurses’ socio-demographic characteristics. Study Design: A descriptive studyPlace and Duration of Study: This study was conducted at the Intensive Care Units at Hilla Teaching Hospital andImam Sadiq Hospital, Babylon Province from 1st January 2023 to 1st April 2023.Methods: A descriptive study was carried out using a non-probability convenience sample consisting of 100 nursesemployed in intensive care units at Hilla Teaching Hospital and Imam Sadiq Hospital, Babylon Province. Data werecollected and divided in two main parts: the first section covered demographic characteristics, while the secondincluded a 16-item scale assessing nurses’ perceptions regarding family participation in patient’s care. Responseswere recorded using a three-point Likert scale (Agree, Neutral, Disagree).Results: Majority of nurses (58%) was aged between 20 and 25 years, 60% were female with 66% held a collegedegree in nursing. Additionally, 56% were married, 80% had five years of clinical experience, and 75% resided inurban areas.Conclusion: Nurses generally maintained a neutral stance toward the involvement of families in patient care withinthe ICU setting and a significant correlation between nurses' perspectives and various demographic factors,including their age, educational background, years of clinical experience, and area of residence.